A practical self-made device in parathyroid autotransplantation for patients with secondary hyperparathyroidism. Issue 1 (January 2019) - Du, Lei; Zhang, Xiwei; Yan, Liang; Zhang, Hao; Tang, Xuefeng; Kong, Xiancheng; Liu, Gang; Huang, Jianping
Objective: Secondary hyperparathyroidism (sHPT) is one of the most serious complications in patients on long-term hemodialysis. These patients may suffer from metabolic bone diseases, severe atherosclerosis, and undesirable cardiovascular events. Endoscopic parathyroidectomy with autotransplantation is a treatment option for those who do not respond to clinical management. This study aimed to investigate practical use of a self-made device in parathyroid autotransplantation for patients with sHPT, and to compare this device with ordinary surgical scissors. Methods: A total of 15 patients with sHPT were treated with endoscopic parathyroidectomy and autotransplantation. Pieces of parathyroid tissue were squeezed in our self-made device and injected into the brachioradialis muscle. Sixteen patients with sHPT who were treated with traditional parathyroid transplantation served as controls. Serum levels of parathyroid hormone, alkaline phosphatase, calcium, phosphorus and intact parathyroid hormone were measured before and after surgery. Results: Preoperative symptoms were alleviated, and serum parathyroid hormone and alkaline phosphatase levels, hyperphosphatemia, and hypercalcemia were improved or normalized in all of the patients in both groups. Pathological examinations showed that parathyroid cells remained active. Conclusion: Application of our squeezing device is an economic, effective, and safe method in endoscopic parathyroidectomy and autotransplantation for patients with sHPT.